Constructing juvenile delinquency: An analysis of news media coverage and government response to youth crime in Malaysia - Kamsiah, Ali (Faculty of Arts & Social Sciences, UNSW, 2012)
This thesis examines the topic of the social construction of juvenile crime in Malaysia. The research project seeks to establish the extent to which youth crime is contextualised and socially constructed as part of perceived ‘social problems’ in Malaysia by various claims makers in society, namely government agencies, the media and the public. The thesis will analyse in particular the construction of claims made in the area of youth crime and the evolution of perceptions of it as becoming a serious and problematic societal issue. Claims made in the newspapers and government documents will form the basis for the examination of the issues.